Finite automaton intrusion tolerance system model based on Markov - Zhiyong LUO; Xu YANG; Guanglu SUN; Zhiqiang XIE; Jiahui LIU (Tongxin xuebao)
To ensure that the system could still provide normal service for legitimate users when the LAN being invaded,a finite automaton intrusion tolerance model was designed.Based on Markov’s theory,the state transformation relationship of the service provided by the system by establishing the state transition probability matrix was described,quantified the transition state and found the key nodes in the system.The maintenance of key nodes could enhance the tolerance of the system and improve the reliability of the service.Experimental comparison shows that this model not only has strong intrusion tolerance,but also has obvious advantages in the integrity of the security system when it is invaded.